An evaluation pf palliative care needs for HIV patients in the context of HAART at Phil Moyo Clinic, Gauteng Province - Eyassu, Melaku Alazar (Department of Public Health and Family Medicine, 2018)
Background: With the introduction of 'highly active antiretroviral therapy' (HAART) HIV/AIDS has been transformed into a more manageable, chronic disease in our days. Despite the advent of effective antiretroviral therapy and its availability in many parts of the world, patients with HIV disease still present many palliative care challenges and problems. These patients continue to have a high burden of pain, other physical and psychological symptoms. The main role of palliative care is to minimize and prevent suffering and maximize physical function and quality of life in patients with serious illness such as HIV/AIDS. AIM: To explore the palliative care needs of adult HIV patients at Philp Moyo clinic Methods: This study utilized a quantitative cross sectional descriptive design which was carried out at Philp Moyo clinic, Ekurhuleni District, Gauteng province. Simple random sampling was used to recruit 162 adult participants. Data was collected using questionnaire by interviewers. Data was analyzed using STATA software version 13 and the analyzed data was presented by means of charts, graphs, and frequency tables. Results. Detail assessment of each symptom at a point of interview using ESAS (0=best and 10=worst) indicated mean score of physical pain was (7), physical symptoms (6), emotional problems such as depression (6) and Anxiety (5) were noted. The prevalence of pain symptoms was the highest (90.7%) followed by depression (87.04%) and anxiety (80.86%). In this study only 30% of respondents were prescribed pain medications for 80% of participants' pain was not treated appropriately. Conclusion: The study showed there is high prevalence of pain and other symptoms indicating a high symptom burden experienced by the participants highlighted the needs of palliative care for ambulant patient population already receiving HAART. It is crucial to understand that palliative care approach is so important to address physical and psychological symptoms experienced by HIV patients.